Reputation: 3929
I have this monadic object.
data Parser a = Parser (String -> Maybe (a, String))
instance Functor Parser where
-- fmap :: (a -> b) -> Parser a -> Parser b
fmap f (Parser pa) = Parser $ \input -> case pa input of
Nothing -> Nothing
Just (a, rest) -> Just (f a, rest)
instance Applicative Parser where
pure = return
(<*>) = ap
instance Monad Parser where
--return :: a -> Parser a
return a = Parser $ \input -> Just (a, input)
--(>>=) :: Parser a -> (a -> Parser b) -> Parser b
(Parser pa) >>= f = Parser $ \input -> case pa input of
Nothing -> Nothing
Just (a,rest) -> parse (f a) rest
And I have this definition of an item
which I am told "reads in a character" but I don't really see any reading going on.
item :: Parser Char
item = Parser $ \ input -> case input of "" -> Nothing
(h:t) -> Just (h, t)
But ok, fine, maybe I should just relax about how literal to take the word "read" and jibe with it. Moving on, I have
failParse :: Parser a
failParse = Parser $ \ input -> Nothing
sat :: (Char -> Bool) -> Parser Char
sat p = do c <- item
if p c
then return c
else failParse
And this is where I get pretty confused. What is getting stored in the variable c
? Since item
is a Parser
with parameter Char
, my first guess is that c
is storing such an object. But after a second of thought I know that's not now the do
notation works, you don't get the monad, you get the contents of the monad. Great, but then that tells me c
is then the function
\ input -> case input of "" -> Nothing
(h:t) -> Just (h, t)
But clearly that's wrong since the next line of the definition of sat
treats c
like a character. Not only is that not what I expect, but it's about three levels of structure down from what I expected! It's not the function, it's not the Maybe
object, and it's not the tuple, but it's the left coordinate of the Just
tuple buried inside the function! How is that little character working all that way outside? What is instructing the <-
to extract this part of the monad?
Upvotes: 4
Views: 404
Reputation: 71099
TL;DR: In general, by Monad laws,
do { item }
is the same as
do { c <- item
; return c
}
so it is defined by a return
, in a sense. Details follow.
It does take one character out from the input string which is being "read", so in this sense it "reads" that character:
item :: Parser Char
item = Parser $ \ input -> -- input :: [Char]
case input of { "" -> Nothing
; (h:t) -> Just (h, t) -- (h:t) :: [Char]
} -- h :: Char t :: [Char]
and I bet there's a definition
parse (Parser pa) input = pa input
defined there somewhere; so
parse item input = case input of { "" -> Nothing
; (h:t) -> Just (h, t) }
Next, what does (>>=)
mean? It means that
parse (Parser pa >>= f) input = case (parse (Parser pa) input) of
Nothing -> Nothing
Just (a, leftovers) -> parse (f a) leftovers
i.e.
parse (item >>= f) input
= case (parse item input) of
Nothing -> Nothing
Just (a, leftovers) -> parse (f a) leftovers
= case (case input of { "" -> Nothing
; (h:t) -> Just (h, t)
}) of
Nothing -> Nothing
Just (a, leftovers) -> parse (f a) leftovers
= case input of
"" -> Nothing
(h:t) -> case Just (h, t) of {
Just (a, leftovers) -> parse (f a) leftovers }
= case input of
"" -> Nothing
(h:t) -> parse (f h) t
Now,
-- sat p: a "satisfies `p`" parser
sat :: (Char -> Bool) -> Parser Char
sat p = do { c <- item -- sat p :: Parser Char
; if p c -- item :: Parser Char, c :: Char
then return c -- return c :: Parser Char
else failParse -- failParse :: Parser Char
}
= item >>= (\ c ->
if p c then return c else failParse)
(by unraveling the do
syntax), and so
parse (sat p) input
= parse (item >>= (\ c ->
if p c then return c else failParse)) input
-- parse (item >>= f) input
-- = case input of { "" -> Nothing ; (h:t) -> parse (f h) t }
= case input of
"" -> Nothing
(h:t) -> parse ((\ c -> if p c then (return c)
else failParse) h) t
= case input of
"" -> Nothing
(c:t) -> parse (if p c then (return c)
else failParse) t
= case input of
"" -> Nothing
(c:t) -> if p c then parse (return c) t
else parse failParse t
= case input of
"" -> Nothing
(c:t) -> if p c then Just (c, t)
else Nothing
Now the meaning of sat p
should be clear: for c
produced by item
(which is the first character in the input, if input is non-empty), if p c
holds, c
is accepted and the parse succeeds, otherwise the parse fails:
sat p = for c from item: -- do { c <- item
if p c -- ; if p c
then return c -- then return c
else failParse -- else failParse }
Upvotes: 2
Reputation: 2066
As comment mentioned, <-
just be do notation syntax sugar and equivalent to:
item >>= (\c->if p c
then return c
else failParse)
Okay, let see what is c
? consider the definition of (>>=)
(>>=) :: Parser a -> (a -> Parser b) -> Parser b
or more readable way:
Parser a >>= (a -> Parser b)
And Now, matches it with above expression item >>= (\c->if p c then return c else failParse)
give:
Parer a = item
and
(a->Parser b) = (\c->if p c then return c else failParse)
and item
has type:
item :: Parser Char
so, we can now replace a
in (>>=)
by Char, gives
Parser Char >>= (Char -> Parser b)
and now \c->if p c then return c else failParse
also have type: (Char -> Parser b)
and so c
is a Char, and the whole expression can be extended to:
sat p =
item >>= (\c->...) =
Parser pa >= (\c->...) = Parser $ \input -> case pa input of
Nothing -> Nothing
Just (a,rest) -> parse (f a) rest
where f c = if p c
then return c
else failParse
pa input = case input of "" -> Nothing
(h:t) -> Just (h, t)
Upvotes: 3